19-46=3(x-4)-3

Simple and best practice solution for 19-46=3(x-4)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19-46=3(x-4)-3 equation:


Simplifying
19 + -46 = 3(x + -4) + -3

Combine like terms: 19 + -46 = -27
-27 = 3(x + -4) + -3

Reorder the terms:
-27 = 3(-4 + x) + -3
-27 = (-4 * 3 + x * 3) + -3
-27 = (-12 + 3x) + -3

Reorder the terms:
-27 = -12 + -3 + 3x

Combine like terms: -12 + -3 = -15
-27 = -15 + 3x

Solving
-27 = -15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-27 + -3x = -15 + 3x + -3x

Combine like terms: 3x + -3x = 0
-27 + -3x = -15 + 0
-27 + -3x = -15

Add '27' to each side of the equation.
-27 + 27 + -3x = -15 + 27

Combine like terms: -27 + 27 = 0
0 + -3x = -15 + 27
-3x = -15 + 27

Combine like terms: -15 + 27 = 12
-3x = 12

Divide each side by '-3'.
x = -4

Simplifying
x = -4

See similar equations:

| -8-6m=-6m-8 | | 3xy+7=15 | | stop=no+hey-ten | | n(n-7)= | | -2x-(x-2)=5x+3(x+1) | | -9+8s=8s-2 | | 3(2x+y)= | | duck+duck=wink | | 65y=32(2y+11) | | 13(x-3)=-6-7 | | .40+.70(100)=.60(100+x) | | 220x-x^2=0 | | 5(y-2)= | | 8/3=h/15 | | x+2=3-4 | | 2x+17=4x-13 | | 3g-3= | | -15x^2+1050x-9000=0 | | D-th=u | | 4t=-t+5t | | 5m(2m+3)= | | x^3y-3x^2y^2-40xy^3=0 | | x^8=656 | | y-x=0 | | 5y+8=20x+43 | | 0.9x-5.6=0.7 | | 12g-7=5 | | (x)(x)-2x-15=0 | | -4(t-3)+7t=8t-2 | | 5(5x-5)+3=25x-22 | | 3/8-m/9=7/72 | | -4x+3y+1=0 |

Equations solver categories